Value-based process project portfolio management: integrated planning of BPM capability development and process improvement - Martin Lehnert; Alexander Linhart; Maximilian Röglinger (Business Research, 2016)
Business process management (BPM) is an important area of organizational design and an acknowledged source of corporate performance. Over the last decades, many approaches, methods, and tools have been proposed to discover, design, analyze, enact, and improve individual processes. At the same time, BPM research has been and still is paying ever more attention to BPM itself and the development of organizations' BPM capability. Little, however, is known about how to develop an organization's BPM capability and improve individual processes in an integrated manner. To address this research gap, we developed a planning model. This planning model intends to assist organizations in determining which BPM- and process-level projects they should implement in which sequence to maximize their firm value, catering for the projects' effects on process performance and for interactions among projects. We adopt the design science research (DSR) paradigm and draw from project portfolio selection as well as value-based management as justificatory knowledge. For this reason, we refer to our approach as value-based process project portfolio management. To evaluate the planning model, we validated its design specification by discussing it against theory-backed design objectives and with BPM experts from different organizations. We also compared the planning model with competing artifacts. Having instantiated the planning model as a software prototype, we validated its applicability and usefulness by conducting a case based on real-world data and by challenging the planning model against accepted evaluation criteria from the DSR literature.
Keywords: 650; Business process management; Capability development; Process decision-making; Process improvement; Project portfolio management; Value-based management